Naskah Jejak Kasih Ibu: Studi Intertekstualitas atas Legenda Si Mardan dari Kota Tanjung Balai - Khairani, Ita; Akbar Fauzi, Russel; Rahma, Fitri; Precillia, Monita (PANGGUNG, 2026)
This study examines the script Jejak Kasih Ibu as an intertextual work derived from the legend of Si Mardan originating from Tanjung Balai, integrated with the phenomenon of overparenting. The focus of this research is to trace the relationships between texts and to analyze how the cultural values embedded in the legend are reinterpreted in accordance with contemporary societal needs. The aim of the study is to understand the interconnection between the script Jejak Kasih Ibu and the legend of Si Mardan as a hypotext, thereby revealing the cultural values and moral messages that have been transformed into a modern theatrical script. The research employs a qualitative descriptive method with Julia Kristeva’s theory of intertextuality as its main analytical framework, emphasizing the dialogic relationships among texts and the shifts in meaning that occur within them. The findings indicate that Jejak Kasih Ibu is not merely a reinterpretation of a traditional legend into a theatrical form, but also serves as a medium for reinforcing the cultural values of the Tanjung Balai community through narratives that are both contextual and relevant to contemporary issues. This study underscores the significant role of literature as a medium of cultural interaction and exchange, as well as a means of preserving local wisdom through an intertextual approach.